2012
DOI: 10.1088/1367-2630/14/3/033004
|View full text |Cite
|
Sign up to set email alerts
|

Doping dependence of gap inhomogeneities at Bi2Sr2CaCu2O8+δsurfaces

Abstract: We study the inhomogeneity of the pairing gap near the surface of Bi 2 Sr 2 CaCu 2 O 8+δ due to interstitial oxygen dopants. Within the slave boson mean-field theory of a disordered t-t -J model, we identify three aspects of the oxygen dopants related to inhomogeneity: (i) the superexchange interaction is locally enhanced in the vicinity of oxygen dopants, which enhances the local pairing gap and reduces the coherence peak; (ii) oxygen dopants donate holes into the CuO 2 plane, which reduces the spinon density… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…This could be due to the decrease in the number of dopant atoms causing a decrease in the scattering that is correlated with  1 . This would leave only the scattering that is correlated with the patchwork boundaries behind and is consistent with the theory that the local  1 value is driven by local exchange or superexchange enhancement 23,42,43 .…”
Section: D Oxygen Dopant Atoms and Tripartite Observablessupporting
confidence: 82%
See 2 more Smart Citations
“…This could be due to the decrease in the number of dopant atoms causing a decrease in the scattering that is correlated with  1 . This would leave only the scattering that is correlated with the patchwork boundaries behind and is consistent with the theory that the local  1 value is driven by local exchange or superexchange enhancement 23,42,43 .…”
Section: D Oxygen Dopant Atoms and Tripartite Observablessupporting
confidence: 82%
“…One possible candidate for the origin of this disorder is cation disorder which is present in this family of cuprates 55 . Regardless of the specific cause of the disorder, the mechanism by which this disorder affects the low energy states can take the form of a change in the local a pairing interaction 36,42 , or a superexchange variation 23,56 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 To reconcile the observed local trend (O i (Bi) hole donors correlated to regions of large ∆) with the global trend (increased hole doping reduces ∆) required a care- fully tuned phenomenological model. 10 Our work provides a more natural explanation to reconcile the local and global trends. We have found that regions of large ∆ are only weakly correlated to O i (Bi), with strongest correlation to AOVs (electron donors) and intermediate correlation to O i (Sr) (hole donors).…”
mentioning
confidence: 78%
“…Theoretical models have argued for the primacy of charge, 8 strain, 9 or a carefully tuned combination of both. 10 A set of strain theories have specifically explored the relationship between the apical oxygen height and the superconducting pairing strength, predicting both enhancement [11][12][13][14] and reduction 15 of pairing strength with increasing apical oxygen height. However, microscopic theoretical understanding of cause and effect has been stalled by uncertainty about the precise dopant locations.…”
mentioning
confidence: 99%